Gender-based analysis of randomized comparison of bioactive versus everolimus-eluting stents in acute coronary syndrome. Issue 3 (March 2015) - Sia, Jussi; Nammas, Wail; Niemelä, Matti; Airaksinen, Juhani K.E.; Lalmand, Jacques; Laine, Mika; Tedjokusumo, Pintoko; Nyman, Kai; Biancari, Fausto; Karjalainen, Pasi P.
Abstract : Aims: The randomized comparison of titanium-nitride-oxide-coated bioactive stent with everolimus-eluting stent in acute coronary syndrome (BASE-ACS) trial demonstrated an outcome of the titanium-nitride-oxide coated bioactive stents (BASs) that was statistically noninferior to that of the everolimus-eluting stents (EESs) at 12-month follow-up, in patients presenting with acute coronary syndrome (ACS) who underwent early percutaneous coronary intervention. We performed a post-hoc gender-based analysis of the BASE-ACS trial at 24-month follow-up. Methods: A total of 827 patients (198 women) with ACS were randomly assigned to receive either BAS or EES. The primary endpoint was a composite of cardiac death, nonfatal myocardial infarction (MI), or ischemia-driven target lesion revascularization. Results: Women were older, and more likely to have diabetes and hypertension compared with men ( P < 0.05 for all). Moreover, women had significantly smaller reference vessel diameter and stent diameter ( P < 0.05 for all). At 24-month follow-up, the cumulative incidence of the primary endpoint was similar between the two sex subgroups (15.2 versus 11.0%, for women versus men, respectively, P = 0.13). However, the rate of nonfatal MI was significantly higher in women compared with men (8.6 versus 3.8%, respectively, P = 0.007). After propensity score-adjusted analysis, there was a trend toward more nonfatal MI among women (8.6 versus 4.0%, respectively, P = 0.08). Moreover, among male patients, those assigned to BAS had significantly lower nonfatal MI compared with those assigned to EES ( P = 0.027). However, among patients assigned to EES, female patients had a significantly higher rate of nonfatal MI compared with men ( P = 0.02). Conclusion: In the current post-hoc gender-based analysis of the BASE-ACS trial, the 24-month outcome of patients undergoing percutaneous coronary intervention for ACS was slightly worse in women, compared with men, as reflected by a trend toward more nonfatal MI events after propensity score-adjusted analysis.